The China-U.S. partnership to prevent spina bifida : the evolution of a landmark epidemiological study - Kowal, Deborah (Vanderbilt University Press, 2015)
"An American-Chinese partnership to prevent spina bifida and related birth defects succeeded through old-fashioned field epidemiology, advocates with influence, and genuine collaboration based on personal relationships built on trust, respect, and shared problem-solving"--Provided by publisher.